Commercially available chromophores as low-cost efficient electron injection layers for organic light emitting diodes. (26th May 2022) - Verykios, Apostolis; Soultati, Anastasia; Tourlouki, Konstantina; Katsogridakis, Charalampos; Alexandropoulos, Dimitris; Vidali, Veroniki P; Panagiotakis, Stylianos; Yannakopoulou, Konstantina; Dimotikali, Dimitra; Fakis, Mihalis; Palilis, Leonidas C; Stathopoulos, Nikolaos; et al.
Abstract: Further advancements in organic light emitting diodes (OLEDs) using commercially available, low-cost materials is of high significance. Here, we report the application of commercially available chromophores as room temperature processed electron injection layers (EILs) in the conventional OLED architecture. The facile solution-processing of these chromophores, namely, 4‐dimethylamino‐4′‐nitrostilbene (DANS) and 1‐(4‐(dimethylamino)phenyl)‐6‐phenyl‐1, 3, 5‐hexatriene, along with the presence of nitrogen atom in their structure, which is expected to induce the formation of a negative interfacial dipole at the cathode interface, have motivated their use as EILs. Improved performance of the OLEDs using these chromophores was obtained. Especially, the OLED using DANS exhibited the highest luminous efficiency, power efficiency and external quantum efficiency values of 8.7 cd A −1, 6.75 lm W −1 and 2.9%, respectively, which represented a significant improvement compared to the reference device without the EIL (1.2 cd A −1, 0.7 lm W −1 and 0.4%, respectively). A variety of experimental and simulated results demonstrated that this enhancement is attributed to increased electron injection leading to balanced electron and hole currents, especially in the DANS embedding device. Additionally, we calculated significant broadening of the emission zone profile across the entire organic emitter in the devices using the chromophores, thus increasing the probability of radiative recombination and photon emission.